RELIGIOUS MODERATION IN THE PERSPECTIVE OF MILLENNIAL STUDENTS IN ISLAMIC BOARDING SCHOOLS - Maula Abdul Affuw Mandat; Muhammad Wildan Shohib (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
This study aims to analyze how religious moderation is implemented at the Hidayatullah Islamic boarding school in Yogyakarta and the role of millennial students at the Hidayatullah Yogyakarta Islamic boarding school in realizing religious moderation. The research method used is descriptive-qualitative, which allows researchers to explore the understanding and meaning behind the development of religious moderation at the Hidayatullah Islamic Boarding School, Yogyakarta. Data was collected through interviews and direct observation at the Islamic boarding school. Research findings show that the Hidayatullah Islamic Boarding School implements religious moderation with the principle of